Degradasi Bahan Kering dan Produksi Asam Lemak Terbang In Vitro pada Kulit Buah Kakao Terfermentasi - Nelson, Nelson (Fakultas Peternakan Universitas Jambi, 2011)
The research was conducted to investigate dry matter degradation and VFA production of fermented cocoa pods by Phanerochaete chrysosporium. The experiment method Completely Randomized Block Design with two factors: three treatment mineral supplementation and four treatment storage length. The result showed that mineral administration had no effect to dry matter degradation, VFA production, ammonia concentration. Fermentation length affected volatile fatty acids with the highest production at day 10. Mineral supplementation to fermented cacao pods had no optimal yield on dry matter degradation, VFA production, and ammonia production.